Prevalence Of Non-Syndromic Hypodontia And Its Association With Malocclusion And Skeletal Morphology - Ismail, Nur Aqilah (2022)
Hypodontia is one of the common dental anomalies influenced by several factors in dental development such as genetic and environmental factors. This study aims to estimate the prevalence and pattern of non-syndromic hypodontia excluding third molars and its association with dental malocclusion and skeletal morphology among orthodontic patients at the AMDI (Advanced Medical and Dental Institute) Orthodontics Specialist Clinic. A total of 630 patients (n = 630) (459 females, 171 males) attending AMDI Orthodontics Specialist Clinic from 2011 to 2019 were assessed. Patients’ data, panoramic radiographs, and study casts were used to identify patients with missing permanent teeth, excluding third molars. TAC Data Analysis Tool method was used to determine the prevalence and pattern of non-syndromic hypodontia excluding third molars. All forty-five dental casts of patients with NSH were assessed by three orthodontic specialists to determine the dental malocclusion for each patient and lateral cephalometric tracing on hypodontia patients was done using the Web Ceph, an artificial intelligence web-based orthodontic and orthognathic platform, to determine the patients' skeletal malocclusion.